Tinjauan Yuridis Hak Asuh Anak Mumayyiz: Studi Putusan Nomor 4283/Pdt.G/2023/Pa.Sby - elverda nadifa rosyadi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
In Article 105 letter (a) of the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI), it is stated that the custody of a child who has not yet reached the age of discernment (mumayyiz), or who is under 12 years old, is the right of the mother. In the event of a divorce, custody of a child under the age of 12 automatically falls to the mother. Meanwhile, according to Article 105 letter (b) of the KHI, a child who has reached the age of discernment may choose whether to be in the custody of the father or the mother. In Decision Number 4283/Pdt.G/2023/PA.Sby, there is a situation where a mumayyiz child chooses someone other than the father or the mother. However, the custody holder of the child is not clearly explained in the ruling. This results in a lack of clarity regarding the legal status of custody for children who have reached the age of discernment.